Biosocial Determinants of Alcohol Risk Behavior: An Epidemiological Study in Urban and Rural Communities of Aligarh, Uttar Pradesh - Sumeet Dixit; M Athar Ansari; Zulfia Khan; Najam Khalique (Medsci Publications, 2012)
Background: Alcohol use disorders are prevalent across all societies. WHO estimates that harmful use of alcohol results in 2.5 million deaths each year and Alcohol is the world's third largest risk factor for disease burden. It is also associated with many serious social and developmental issues, including violence, child neglect/abuse, and absenteeism in the workplace which necessitates information on quantum and pattern of alcohol use, for effective behavior change interventions. Methods: The cross sectional survey was conducted over a period of one year among 848 individuals (≥15 years) from urban and rural field practicing areas of the department of community medicine, JNMCH, AMU, Aligarh. Door to door survey was done. Households were the primary sampling unit. Data analysis has been done using SPSS version 14.0. To test significance chi square test have been used as applicable. Results: Prevalence for alcohol use was 13.4% (including current and ever user both). 43(5.07%) of study subjects were current alcohol users and 71(8.37%) were categorized as ever users for alcohol. Alcohol use was found significantly associated with age, sex, socio-economic status, occupation, religion, caste, parental alcohol use, and rural residence. Conclusions: The study documented prevalence, patterns of use and determinants of alcohol risk behavior. Efforts, targeting the most vulnerable and using Health promotion, health education and behavior change communication as tools, can prove valuable for effective control of alcohol risk behavior and related mortality/morbidity.